ANALISIS FAKTOR-FAKTOR YANG MENGAKIBATKAN KEMACETAN LALU LINTAS PADA RUAS JALAN BUDI UTOMO DAN JALAN HASANNUDIN DI KOTA TIMIKA - Tri Apriyono; Dionisius Paskalis Rumlus (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2021)
This study aims: to determine the relationship between the factors of road facilities and infrastructure, vehicle regulation, vehicle speed regulation, road user behavior and traffic regulation with the level of traffic congestion on the Budi Utomo and Hasannudin roads and to determine the dominant factors causing traffic congestion. traffic on Jalan Budi Utomo and Jalan Hasannudin in Timika City. The method used is a descriptive method with a quantitative approach. The instrument used in data analysis is factor analysis. The results showed that the factors that caused traffic congestion on Budi Utomo and Hasannudin roads were road facilities and infrastructure factors, vehicle regulation, vehicle speed regulation, road user behavior and traffic regulation. Budi Utomo and Hasannudin Timika roads are the behavior of road users.